(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
The otoliths described here from the Late Santonian of the Eutaw Formation of Alabama, represent one of the earliest association of teleost otoliths known from North America and it is remarkable for its good preservation and species diversity. They were collected by the late C.K. Lamber in 1969 from a road cut on the Hurtsboro-Marvyn highway south of Marvyn in Russell County, eastern Alabama. It contains 18 taxa based on sagittae otoliths, of which 14 are identifiable to the species level, 10 species are new to science and five new genera. The new otolith-based genera are: Allogenartina n. gen. (Stomiiformes family indet.), Pseudotrichiurus n. gen. (Aulopiformes family indet.), Eutawichthys n. gen. (Beryciformes family indet.), Cowetaichthys n. gen. (Polymixiidae) and Vox n. gen. (Teleostei family indet.); the new species are: Elops eutawanus n. sp., Genartina cretacea n. sp., Allogenartina muscogeei n. sp., Pseudotrichiurus sagax n. sp., Apateodus? assisi n. sp., Eutawichthys compressus n. sp., Eutawichthys stringeri n. sp., Cowetaichthys alabamae n. sp., Cowetaichthys lamberi n. sp. and Vox thlotlo n. sp. In addition, 8 different morphologies are recognized based on lapilli otoliths, which however cannot be identified to a distinct taxonomic level except for a species of the Ariidae. Two taxa can be related to otoliths recently recorded in situ, pertaining to the genera Osmeroides and Apateodus. The otolith association bears much similarity with those of the Campanian to Maastrichtian of the USA described previously as indicated by the dominance of otoliths of the genera Eutawichthys and Osmeroides. Differences with those faunas are on the species level as well as in the accessory components. The abundance of otoliths of the albuliforms (Osmeroides), putative stomiiforms (Allogenartina), beryciform (Eutawichthys) and polymixiids (Cowetaichthys) characterizes a rather stable faunal composition through the entire Late Cretaceous of locations studied in the USA. The conundrum of interpreting the systematic position of isolated Late Cretaceous otoliths is discussed and the findings are correlated with the rich fish fauna known from articulated skeletons of the coeval Niobrara Formation. We consider the taxonomic position of the majority of isolated otoliths to be more or less consistent with the skeletal findings, but there are also a few otolith morphologies, which do not seem to have a skeletal equivalent in the Niobrara Formation, e.g. in osteoglossiforms, clupeiforms, stomiiforms and Ariidae.